(untitled) (Research, Society and Development, 2020)
Objective: to relate physical exercise to the reduction of insulin resistance in type 2 diabetic individuals. Methodology: the bibliographic survey carried out was developed through a retrospective observational study or experimental study of recovery and critical analysis of the literature. Results: it is observed that the regular practice of physical activities of lesser or greater intensity has beneficial effects on diabetic individuals, with a reduction in glycemic levels and an increase in insulin sensitivity. Conclusion: it is concluded that the practice of exercises is an ally in the treatment of type 2 diabetes.